"And how is life going for you?"—an account of subjective welfare in medicine. Issue 10 (28th September 2007) - Molyneux, David
Abstract : The dominant account of welfare in medicine is an objective one; welfare consists of certain favoured health states, or in having needs satisfied, or in certain capabilities and functionings. By contrast, I present a subjective account of welfare, suggested initially by LW Sumner and called "authentic happiness". The adoption of such an account of welfare within medicine offers several advantages over other subjective and objective accounts, and systematises several intuitions about patient-centredness and autonomy. Subjective accounts of welfare are unpopular because of their implications for justice and the autonomy of the healthcare professional. This account of welfare, however, seems to have the resources to resist these criticisms.